When internationalization goes awry: The separation of policy and practice in intellectual property - Mandrinos, S.; Cheong, Calvin W. H. * (Routledge, 2022)
Internationalization contributes to economic growth and as a result, many nations seek to encourage it by liberalizing domestic business environments and standardizing trade policies with other nations. However, in their attempt to standardize policy, some nations – through regulatory authority – (un)willingly adopt a heavy-handed approach, creating institutional pressures that stifle firm-level decisions, to align firm interests with those of the state. Inconsistencies in the framing and enforcement of laws and standards meanwhile, create institutional complexities. Both institutional pressures and complexities force firms to devise strategic responses that ultimately result in either an (un)intentional decoupling, or (in)voluntary de-internationalization. In this chapter, we discuss these concepts in the context of Sino-American trade relations and the intellectual property rights (IPRs) issues, before providing a conceptual framework that will help form the basis of further analysis on firm strategic responses to institutional pressures and complexities.